Microplastic presence in blue mussels (Mytilus edulis) from the Westfjords, Iceland - Robyn Annaly De Bruijn 1998- (2024)
This study aimed to look at the presence of microplastics in mussels from the Westfjords, specifically aimed to look at the effect of urbanization and water flow on the presence of microplastics in blue mussels (Mytilus edulis), as well as inspecting a temporal aspect. It also discusses the usage of Hot Needle Testing (HNT) as a method to identify microplastics. Blue mussels were collected from three distinct locations within the Westfjords, two of which were in the rural town of Ísafjörður. The first was connected to open water, while the other was situated in the ‘Pollurinn,’ where water flow is limited. The third location was in a fjord further away with limited human activity, except for a single nearby farm. After collection, mussel samples underwent chemical digestion followed by filtering through a 2.7µm glass fiber filter and plastic identification using HNT to detect the presence of microplastics. The study compared the sizes, shapes, and colors of microplastics found across the sampled locations in order to quantify differences based on the effect of urbanization, water flow and time. Microplastics were present at all locations. Out of the 60 mussels studied, 68.3% contained at least one microplastic. The frequency of bead, fiber or fragment microplastic found did not differ significantly between locations. The microplastics found were between 0.3 and 4.2mm in size and the colors black and dark blue were most commonly found. The color of the microplastic could suggest information about the plastic origin. Urbanization was found to have limited effect on the microplastic presence in the mussels, significantly more microplastics were found in mussels from one of the urban locations compared to the remote location. Mussels from the location with better water flow contained more and larger microplastics. This could mean that the presence of microplastics is not only coming from a local source, but also brought over by currents. Hot needle testing can accurately identify plastic 70% of the time, and has in ...